2022
DOI: 10.1038/s41598-022-24107-7
|View full text |Cite
|
Sign up to set email alerts
|

Current global population size, post-whaling trend and historical trajectory of sperm whales

Abstract: The sperm whale lives in most deep ice-free waters of the globe. It was targeted during two periods of whaling peaking in the 1840’s and 1960’s. Using a habitat suitability model, we extrapolated estimates of abundance from visual and acoustic surveys to give a global estimate of 736,053 sperm whales (CV = 0.218) in 1993. Estimates of trends in the post-whaling era suggest that: whaling, by affecting the sex ratio and/or the social cohesion of females, reduced recovery rates well after whaling ceased; preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
0
21
0
2
Order By: Relevance
“…Long-term outcomes (years to decades) Target species Unlike pinnipeds, for which population assessments have been conducted on a regular basis throughout Galaṕagos (e.g., Paéz-Rosas et al, 2021), very few studies have reported population assessments for cetaceans in Galaṕagos (Palacios and Forney, 2008;O'Hern et al, 2017;Whitehead and Shin, 2022), and there is no formal ongoing program for monitoring cetacean populations. Yet, baseline information on demographic parameters, such as density, abundance, survival, and recruitment, is essential for understanding population status and dynamics, and to unravel the relative importance of competition and predation in structuring the local cetacean community relative to the influences of environmental variability.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…Long-term outcomes (years to decades) Target species Unlike pinnipeds, for which population assessments have been conducted on a regular basis throughout Galaṕagos (e.g., Paéz-Rosas et al, 2021), very few studies have reported population assessments for cetaceans in Galaṕagos (Palacios and Forney, 2008;O'Hern et al, 2017;Whitehead and Shin, 2022), and there is no formal ongoing program for monitoring cetacean populations. Yet, baseline information on demographic parameters, such as density, abundance, survival, and recruitment, is essential for understanding population status and dynamics, and to unravel the relative importance of competition and predation in structuring the local cetacean community relative to the influences of environmental variability.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…Worldwide and for up to three centuries, this species was the focus of two intensive hunting periods (Whitehead, 2002). From a pre‐whaling abundance of over 1 million, today there are an estimated 844,761 individuals (Whitehead & Shin, 2022) and they are now globally classified as Vulnerable on the IUCN red list (Taylor et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From a pre-whaling abundance of over 1 million, today there are an estimated 844,761 individuals (Whitehead & Shin, 2022) and they are now globally classified as Vulnerable on the IUCN red list (Taylor et al, 2019). Range-wide population genetic studies of sperm whales have identified several key features.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm whales are globally classified as Vulnerable by the International Union for Conservation of Nature, with an unknown worldwide population trend (Taylor et al, 2019), with recent studies indicating a global population of 844 761 individuals (Whitehead & Shin, 2022). This species was extensively hunted worldwide since the 18 th century, growing from a shore-based enterprise to industrial whaling that only ceased in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…This species was extensively hunted worldwide since the 18 th century, growing from a shore-based enterprise to industrial whaling that only ceased in the 1980s. This caused a decrease of 68% in the global population, with males being more heavily targeted (Whitehead, 2002;Whitehead, 2018). Due to the low reproduction rates of these long-lived mammals, the populations of sperm whales are still recovering.…”
Section: Introductionmentioning
confidence: 99%